Latin American Thinkers of Peace
XII, 186 p. 1 illus.
Keywords: “This welcomed and important book immensely enriches the literatures on peace studies, Global IR, and Latin American contributions to international society. It focuses upon seven Latin American Nobel Peace recipients ranging from Carlos Saavedra Lamas (1936) to Juan Manuel Santos (2016), and their impact on ideas and practices of peace in Latin America and beyond, including issue-areas such as mediation and diplomacy, human rights, nuclear disarmament, indigenous rights, peacekeeping, reconciliation, and ending civil wars.” — Prof. Arie M. Kacowicz, Chaim Weizmann Chair in International Relations, Hebrew University of Jerusalem, Israel “From the social activism of Rigoberta Menchú to the global initiatives of UN Secretary-General Javier Pérez de Cuéllar, this book explores the connection between the power of ideas and the actions of peace leaders to build a better world. The authors’ analyses serve as a reminder to academics and diplomats of the importance of taking small and large steps to manage and transform conflict and create institutions with a human focus.” — Ambassador Claudia Fuentes Julio, Permanent Representative of Chile to the United Nations and other International Organizations in Geneva, Switzerland This book analyzes the contributions of seven Latin American peace actors to reconciliation and conflict resolution: Carlos Saavedra Lamas, Adolfo Pérez Esquivel, Alfonso García Robles, Óscar Arias Sánchez, Rigoberta Menchú Tum, Juan Manuel Santos, and Javier Pérez de Cuéllar. Working within an eclectic conceptual approach to systematize the difusion of their ideas, the chapters build upon three fundamentals of mainstream constructivism: a) change across time and space in each peace actor’s lifetime; b) socialization through changing norms, rules, and language; and c) processes of interaction in which they chose strategies and built networks. In their respective historical times, their views and ideas transcended the confines of Latin America to influence global political thought and produce change that favored peace. Roberto Domínguez is Professor of International Relations at Suffolk University, USA. Andrea Oelsner is Associate Professor and Director of the Political Science and IR Programs at the University of San Andrés, Argentina.